The Role of Family Socialization in Reducing Children's Delinquency due to Social Media Websites: A field study in Al-Hofuf city, Al-Ahsa Governorate - Al-Mari, Ahad Abdel-Hadi; Elmobark, Ummeliz Yousif (Dirasat: Human and Social Sciences, 2024)
Objective: This study aims to explore the role of family social upbringing in reducing children's deviation due to social media websites. Method: The study employed a descriptive-analytical approach. The study community consisted of families in Al Hofuf city, which has elementary school students. There are a total of 44 public girls' schools in the city, and four schools were randomly selected, representing 10% of the total schools. The total number of students in these four schools was 1921 students, and 449 families were chosen from these students' families using systematic random sampling, representing 23% of the total number of families. A questionnaire was used as the primary data collection tool. Conclusions: The results of the field study indicated that proper family social upbringing plays a significant role in reducing children's deviation due to social media sites. This was evident through the high agreement levels in the two main aspects of the family's role: "filling family leisure time" and "monitoring children." Recommendations: The study recommends emphasizing the family's role in reducing children's deviation due to social media sites can be achieved by families following some proper family social upbringing methods, such as monitoring children's social media activities and filling the child's free time with beneficial activities to reduce social media usage.